Evolution and Determinants of Consumer Interest in Renewable Energy in Ecuador: A Temporal Perspective - Vera Arroyo, Diana Margarita; Garcés Wila, Mariuxi Elizabeth; Argandoña Moreira, José Gilberto; Gresely Santi, Francisco Abel; Cárdenas-Ruperti, Jonathan Patricio (International Journal of Energy Economics and Policy, 2024)
Through an empirical analysis of the evolution of Ecuadorian consumers' interest in renewable energy and the factors influencing it, this study seeks to provide an understanding of the popularity and uptake of clean energy in a Latin American country with a significant renewable energy sector. Relevant data on economic and socio-environmental variables were collected and the effect of these variables on indicators of consumer interest in renewable energy was evaluated. The results indicate that Ecuadorian consumers' interest in renewable energy has shown a growth trend in recent years and is influenced by multiple factors, such as the relative production of renewable energy, energy prices and information about natural disasters. Overall, this research contributes to understanding the dynamics of public interest in renewable energy in developing economies such as Ecuador, emphasizing the importance of understanding the evolution of consumer perspective considering not only cost-benefit relationships but also responses to environmental events.